Ceramic Production and Social Change: Archeometric Analysis of Bronze Age Pottery from Jordan - Knapp, A. Bernard; Duerden, P.; Wright, R.V.S.; Grave, P. (Journal of Mediterranean Archaeology, 1988)
An abundance of Fine Ware excavated in Middle and Late Bronze Age levels at Pella in Jordan prompted suggestions of local production. Excavations in Middle Bronze Age levels at nearby Tell el-Hayyat uncovered indisputable, contemporary evidence of ceramic production. Using PIXE-PIGME and NAA, 58 ceramic samples from both sites and 33 local clay samples were investigated in an attempt to establish a chemical profile of local ceramic ’pastes’. Statistical analyses (Principal Components Analysis [PCA] and Cluster Analysis) were conducted on the resultant data sets to evaluate the possibility of local Fine Ware production in the North Jordan Valley. The analytical program, its objectives, and outcome assessed the comparability and utility of PIXEPIGME and NAA in isolating and distinguishing pottery types and clay sources. While archaeometric analysis was therefore employed toward traditional ends, i.e. to distinguish between various possible (local or nonlocal) production loci, PCA results-combined with a theoretical framework loosely based on the concept of ’Ceramic Ecology’-allowcd discussion of the organization of local ceramic production at Pella and Tell el-Hayyat, its impact on the regional economy, and the relationship between ceramic change and social change in emergent complex societies.